Climate Benefits from Methane Mitigation - Sofia Eirini Paschou; Alkiviadis Kalisoras; Prodromos Zanis (Environmental Sciences Proceedings, 2023)
Methane is a greenhouse gas with a lifespan of about a decade, and its presence in the atmosphere affects the Earth’s temperature and the climate system. Methane is included in short-lived climate forcers (SLCFs) or near-term climate forcers (NTCFs), whose atmospheric composition changes have a near-term effect on climate, predominantly in the first two decades after their emission or formation. In this study, the climate benefits of methane mitigation on global air temperature distribution are examined for the near future (2031–2050). The analysis is based on model simulations conducted by the Earth System Model GFDL-ESM4 for the future scenario SSP3-7.0 with additional air quality mitigation measures either in non-methane NTCFs (aerosol and ozone precursors) or in all NTCFs (including methane). It is shown that additional methane mitigation would potentially further contribute to offsetting the warming from reduced aerosols associated mainly with SO2 reductions that would accompany decarbonization.